The Learning Strategies in English Subject of Islamic Study Program at IAIN CURUP - Meilinda, Sri; Noviyenty, Leffy; Apriani, Eka (Yayasan Corolla Education Centre, 2021)
The research objective was to find out the PAI students‟ strategies in learning English. The design of the research was presented in quantitative descriptive. The subject of this research was 2nd semester of PAI department students. To know what strategies used, the researcher used Stern theory about Language learning strategies which are divided into five categories namely management and planning, cognitive, communication, interpretational and affective. In collecting the data, the researcher used close-ended questionnaire. The result show that PAI students who got A score used 4 strategies in learning English they are management and planning strategies, cognitive strategies communicative strategies and affective strategies. But affective strategy is more dominant 83.7% as a strategy in learning English. PAI students who got B scores used 3 strategies in learning English they are management and planning strategies, cognitive strategies and affective strategies. Management and planning strategy is more dominant 74.4% as a strategy in learning English. PAI student who got C score 3 strategies in learning English they are cognitive strategies communicative strategies and affective strategies. But cognitive is more dominant 76% as a strategy in learning English. PAI student who got E score used 2 strategies in learning English they are interpretational strategies and affective strategies. But affective strategy is more dominant 90% as a strategy in learning English. Although, the strategies used by student who got A score and E score are alike, however students who got E score do not attend the class, the UTS and UAS properly.